Career mobility of employees with disabilities in a Gauteng-based state-owned enterprise - Modise, Catherine Mmanare (Vaal University of Technology, 2022)
This study noted the implications of the absence of a strategic framework to manage the career mobility of employees with disabilities in the Gauteng-based, state-owned enterprise (SOE). In response to the limited research on career mobility of employees with disabilities (EwDs), the study aimed to investigate EwDs understanding of the phenomenon, identify its enablers and inhibitors, as well as propose a strategic framework for managing it. The study is significant for the inclusion of EwDs and contributing to employers achieving employment equity targets, as required of them by the Employment Equity Act (55 of 1998). In order to achieve the study’s objectives, an exploratory design was employed by conducting individual interviews with five purposively selected participants on junior management levels. A semi-structured interview schedule was developed and piloted with two champions who represent the interests of EwDs in disability forums within the SOE. Given the prevailing circumstances of the COVID-19 pandemic, the researcher collected the data online via Microsoft Teams (MS Teams). The data were analysed manually for emerging themes using Braun and Clarke’s six steps of data analysis. The study found that career mobility was understood by participants to include promotion (job change), succession planning and gainful employment supported by opportunities for skills transfer and reasonable accommodation. Factors identified as enablers of career mobility are training and career development, disability awareness and sensitisation, reasonable accommodation, social networks and benchmarking. Those factors perceived as inhibiting career mobility are mind-set, inaccessible training, lack of confidence and poor succession planning. Through conversations with the participants, the researcher identified critical components for the development of a strategic framework to enhance career mobility for EwDs as organisational diagnostics (input factor), enabling policies and support systems (process factors) and inclusion and career mobility evident in employment equity targets being met (outcomes) to manage career mobility of EwDs in the workplace. The main limitations of the study are that the results cannot be generalised to other settings without validation of the proposed strategic framework due to the sample size involved. It is recommended that future studies consider sensitivity regarding the prevailing circumstances around research during periods of pandemics and the use of language in the field of disability research. It is further recommended that employers consider implementing benchmarked disability awareness and sensitisation programmes to create a conducive environment for EwDs to achieve career mobility in the workplace. Lastly, employers should develop and implement programmes that will enhance mental health and well-being of EwDs and consider the establishment of empowered disability forums.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Employees with disabilities; Career mobility; Inclusion; Strategic framework; Employment equity; Dissertations, Academic -- South Africa.; People with disabilities -- Employment -- South Africa.; Vocational guidance -- South Africa.; Government business enterprises -- South Africa.; South Africa. -- Employment Equity Act, 1998.